SUMATRAN WERETIGER, CINDAKU: DESIGNING A 3D GAME CHARACTER ANIMATION FOR BANDUNG YOUTH BASED ON MYTHOLOGY FROM KERINCI, JAMBI - Aufar, Achmad Rafidani; Rahadianto, Irfan Dwi; Adharamadinka, Muhammad (eProceedings of Art & Design, 2024)
Cindaku is a tiger mythology from Sumatra, Jambi, Kerinci. Cindaku is seen as the protector of the Kerinci forest. It is important to preserve the cultural values of a mythology like} Cindaku, especially when it talks about protecting the environment and the balance of nature. and the balance of nature. This research aims to find the cultural values that are Cindaku mythology and create a 3D animation game based on these values. values. The animation was then implemented into a game proto}pe. The media video game was chosen because it has been proven to be effective in education. Method This research uses literature study, interviews, and questionnaires for data collection. data collection. This research produced a 3D game animation based on Cindaku and its values, the animation is incorporated into a game proto}pe that can be played on Android devices, especially for mobile phones. Android devices, especially for mobile phones. Keywords: Cindaku, tiger man, game animation, Sumatera